(untitled) (Third Sector Social Economic Review, 2023)
The oilseed plant with the largest cultivation area and production amount in Turkey is sunflower. However, this production is not at a level to meet consumption. It is aimed to meet the need for oil sunflower in the country with domestic resources, to meet the need for vegetable oil, and to ensure sustainability in sunflower production, and incentive policies are implemented in this context. One of the areas covered by sunflower production incentive policies is Eskipazar district of Karabük province. The district has suitable conditions in terms of the ecological demands of the sunflower (oil) plant and agricultural lands with the potential to obtain high yields from sunflower cultivation. The study was carried out in order to bring the non-agricultural areas into agricultural production in Eskipazar district and to determine the areas suitable for sunflower (oil) cultivation in Eskipazar district. In the study, the Analytical Hierarchy Process (AHP) method, one of the Multi-Criteria Decision Making (MCDM) techniques, was used by integrating with Geographic Information Systems (GIS). The weights of the sub-criteria determined for the analysis were calculated and a suitability map was created by combining these criteria. In the analysis, the district’s suitability values for sunflower cultivation were classified as ""Very Suitable"", ""Medium Suitable"", ""Suitable"" and ""Less Suitable"". When the areas where sunflower cultivation is done in the district are compared with the agricultural suitability map, it is seen that these areas overlap with the areas classified as ""Very Suitable"" and ""Medium Suitable"" on the map. In addition, areas in the district that are in the ""Very Suitable"" and ""Medium Suitable"" classes for sunflower cultivation but where sunflower cultivation is not practiced have been identified. Utilizing these fields for sunflower cultivation will increase sunflower production in the district and contribute to reducing the oil sunflower and vegetable oil deficit throughout the country.